COMPARISON OF OPTICAL AND X-RAY MASS ESTIMATES OF THE CHANDRA GALAXY CLUSTERS AT Z < 0.1 - Babyk, Iu. V.; Vavilova, I. B. (Одеські астрономічні публікації, 2013)
We used the optical data taken from SDSS DR7 galaxy and group catalog to determine the optical mass of 37 nearer Chandra galaxy clusters for comparison with the X-ray mass estimates. Using the assumption that mass follows the galaxy distribution, we computed the mass of each cluster by applying the virial theorem to the member galaxies. We have found a good agreement between optical and X-ray mass estimates and confirm that about 70 % of nearby galaxy clusters are not far from dynamical equilibrium.